Effect of Material Composition on Freeze-Thaw Resistance of Asphalt Fine Aggregate Matrix at Low-Temperatures From Mesoscopic Perspective - Gong, Xiangbing; Zheng, Heqi; Liu, Wei; Li, Xi (Frontiers in Materials, 2022)
To explore the significant factors related to the cracking resistance at low temperatures of asphalt mixture from mesoscopic perspective, asphalt fine aggregate matrix (FAM) was selected as the researched material because of its important role in mesoscopic structure of asphalt mixture. Bending Beam Rheometer (BBR) was utilized to investigate low-temperature properties of FAM. Due to the frequent occurrence of freeze-thaw action in seasonally frozen regions, this paper introduces a freeze-thaw cycle test. The structural characteristics of internal air voids in FAM and hot-mix asphalt (HMA) were analyzed using the industrial Computed Tomography (CT). Results indicate that frost heaving damage of FAM-2.36 is more obvious than that of FAM-1.18, and the damage level increases as the bath temperature rises. After 32 freeze-thaw cycles, FAM-1.18 exhibits the rise of creep stiffness than original beams, and the hardening degree become serious with the decease of temperature. It could be concluded that the BBR has been proved to be an effective tool in evaluating the low-temperature properties of FAM. The expanding limit of small air voids and the hardening of binder in rich asphalt FAM contribute to completely different mechanisms of freezing-thawing damage within FAM. Therefore, asphalt content, fine aggregate passing rate and air voids size could be optimized through BBR test of FAM subjected to freeze-thaw cycle.